Youth Speaks Up: Perceived Communication Changes Experienced by Grade 6 Participants in a Personal Development Program - Brann-Barrett, M. Tanya (Alberta Journal of Educational Research, 2005)
A nine-month program entitled Youth Speaks Up is delivered annually to grade 6 students from Sydney, Nova Scotia. One goal of the program is to provide an opportunity for the development of positive communication skills in participants. The purpose of this project was to determine if students participating in the program perceived changes in their communication ability and comfort level as a result of participation in the program. Qualitative focus groups were conducted, and responses suggest that many participants experienced positive changes in their communication comfort levels in public and interpersonal communication contexts, and specifically in their ability and willingness to express their ideas. Participants believed factors such as consistent practice and interaction with new people influenced the changes. Students’ recommendations for program development are also presented.